Restaurações classe ii mod em molares empregando resinas compostas de incremento único e técnica incremental análise biomecânica experimental e computacional - Rosatto, Camila Maria Peres de (2015)
The aim of this study was to evaluate the use of bulk-fill composite resins compared to oblique incremental technique to restore molars with large structural loss. Seventy-five molars were prepared with class II mesial-occlusaldistal (MOD) cavities, restored and divided into 5 groups (n = 15): Z350XT as the control group, restored oblique incremental technique with nanofiller composite Filtek Z350XT (3M ESPE); and 4 techniques using bulk-fill composites: FBF/Z350XT, Filtek Bulk Fill/Filtek Z350XT (3M ESPE); VBF/CHA, Venus Bulk Fill/Charisma Diamond (Heraeus Kulzer); SDR/EST-X, SDR/Esthet- X HD (Dentsply); TEC, TetricEvoCeram Bulk Fill (Ivoclar Vivadent), according each manufacturer s instructions. Ten teeth of each group were used to evaluate the biomechanical behavior and the other five to evaluation Vickers hardness (VHN)/elastic modulus (E). Cusp strain was measured, using straingauge test, in three moments: during the restorations, simulating occlusal loading from 0 to 100N and at the fracture. Teeth transillumination was carried to detect the presence and propagation of enamel cracks. The resin radiodensity and the presence of bubbles into restorations were measured by digitized radiography. After mechanical cycling, fracture resistance using occlusal axial loading and the failure modes were classified by three evaluators. The gel shrinkage, diametral tensile strength and compression strength properties of each seven composite resins (n = 10) were obtained. Finite element analysis was developed using two-dimensional models for definition of residual shrinkage stress and cuspal strain, validating the laboratory findings. Bulk-fill composite resins showed lower polymerization shrinkage, cusp strain and residual stress compared with conventional composite resin. The occurrence of cracks was higher after the restorative procedure regardless of the restorative technique and cusp type. However, the lingual cusp showed more cracks that buccal cusp. The TEC and VBF/CHA had significantly higher radiodensity than the other materials. No difference was found between FBF/Z350XT and Z350XT. TEC and FBF/Z350XT had the similar absolute and relative risk of bubbles presence risk as the Z350XT. VBF/CHA and SDR/EXT-X had significantly lower risk than incremental restoration with Z350XT. Although, the bulk-fill in general had inferior mechanical properties such as tensile strength, compressive strength, Vickers hardness and elastic modulus, they results in higher fracture resistance than incremental technique using nanofiller composite resin. It can be concluded that bulk-fill composite resins are suitable for clinical use in order to minimize the undesirable effects of restorative procedure associated technical simplification.